Exploration of the factors influencing hearing disability in older adults of China: a nested case-control study - Zhou, Wan-Qiong; Liu, Jing; Gao, Yi-Tian; Zhou, Lan-Shu (Frontiers in Public Health, 2024)
Objective As two line trends – aging disability and disability aging – continue to emerge, hearing disability is becoming increasingly prevalent among older adults in china. This study aimed to investigate the incidence of hearing disability among older adults and identify the various factors contributing to its development. Methods In this matched nested case-control study, data from the China Health and Retirement Longitudinal Study from 2011 to 2018 were analyzed. A total of 4,523 older adults were recruited from a national sample database, of which 1,094 individuals were eligible for inclusion in the hearing disability cohort, while 3,429 older adults who had not been diagnosed with hearing disability were considered non-hearing disability controls. Hearing disability was assessed by a self-reported question. These controls were matched to hearing disability cases in a 1:1 ratio based on age and sex. The logistic regression models were used to find out various factors of hearing disability in the target population. Results Totally 1,094 individuals (24.14%) developed hearing disability during the follow-up period. After 1:1 matching, 2,182 subjects were included in the study, with 1,091 cases in the case group. Factors that influenced the incidence of hearing disability in older adults included annual per capita household income (OR = 0.985, p = 0.003), cognitive function (OR = 0.982, p = 0.015), depression level (OR = 1.027, p < 0.001), somatic mobility (OR = 0.946, p = 0.007), history of kidney disease (OR = 1.659, p < 0.001), history of asthma (OR = 1.527, p = 0.008), history of accidental injuries (OR = 1.348, p = 0.015), whether there is a place for recreational and fitness activities in the community (OR = 0.672, p < 0.001), and whether there is a health service center/health center in the community (OR = 0.882, p = 0.006). Conclusion The incidence of hearing disabilities among older adults in China is high. The protective and risk factors that contribute to the incidence of disability should be fully considered in the care of older adults.